AGROBIOLOGICAL CHARACTERISTICS OF THE MALTING SPRING BARLEY CULTIVAR 'OMSKY 100 - P. N. Nikolaev; P. V. Popolzukhin; N. I. Anisimov; O. A. Yusova; I. V. Safonova (Труды по прикладной ботанике, генетике и селекции)
Characteristics of the new malting spring barley cultivar ‘Omsky 100’ are presented. This cultivar, bred at the Siberian Research Institute of Agriculture and submitted for State Trials in 2015, represents the forest-steppe environmental group of varieties. It is characterized by high resistance to lodging, low susceptibility to false loose smut, medium to loose smut, and high to covered smut. As for productivity, 'Omsky 100' is among the high-yielding cultivars in the environments of West Siberia (4.5 t/ha, "+"0.4 t/ha st.). It is responsive to improvement of cultivation conditions (regression coefficient = 2.3; multiplier coefficient = 2.6) and is able to combine high potential yield with its minimal decrease in adverse cultivation environments (homeostaticity = 0.4). Its biochemical indicators correspond to the requirements of the State Standard for malting barley, and it is recommended for use in brewing industry. Key words: common spring barley, growing season, smut incidence, plant height, spike shape, awn serration, kernel color, stability, flexibility, homeostaticity.